1993
DOI: 10.1007/bf00217463
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the 5? region of coagulation factor VII gene (F7) caused by an inserted decanucleotide

Abstract: We describe a polymorphism in the 5' region of the coagulation factor VII (FVII) gene, originating from a decanucleotide (CCTATATCCT) insert present in the less frequent allele. This marker can be detected by restriction analysis of polymerase chain reaction products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 4 publications
0
64
0
1
Order By: Relevance
“…There are two common genetic polymorphisms of coagulation factor VII, both of which are known to lower the plasma factor VII activity: one is the replacement of arginine at 353 with glutamine in the catalytic region on Exon 8 (R353Q) (Green et al 1991) and the other is a 10-base pair (CCTATATCCT) insertion in the promoter region at position -323 (-323P0/10) (Marchetti et al 1993). It has been assumed that the plasma concentration of factor VII is lowered due to an impaired secretion level of factor VII in the R353Q variant (Hunault et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two common genetic polymorphisms of coagulation factor VII, both of which are known to lower the plasma factor VII activity: one is the replacement of arginine at 353 with glutamine in the catalytic region on Exon 8 (R353Q) (Green et al 1991) and the other is a 10-base pair (CCTATATCCT) insertion in the promoter region at position -323 (-323P0/10) (Marchetti et al 1993). It has been assumed that the plasma concentration of factor VII is lowered due to an impaired secretion level of factor VII in the R353Q variant (Hunault et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several insertion-deletion and single-point mutations in the factor VII gene have been reported in the promoter region (e.g., -323P0/10 [a 10-bp insertion in the promoter region at position -323]) and within the proteincoding region (e.g., R353Q point mutation [the replacement of arginine with glutamine at residue 353]); those polymorphisms are known to affect either the function of the protein product or its level of expression (Green et al 1991;Marchetti et al 1993). In addition, the risk of spontaneous intracranial hemorrhage has been suggested to be linked to the factor VII polymorphism -323P0/10 in adults (Corral et al 2001).…”
Section: Blood Sampling and Normotestmentioning
confidence: 99%
“…Within the FVII gene eight polymorphisms are known (Herrmann et al, 1998;Herrmann et al, 2000) and three of them influence the level of FVII activity: the insertion polymorphism of the promotor (Marchetti et al, 1993), a tandem repeat unit polymorphism within intron 7 (Marchetti et al, 1991;de Knijff et al, 1994;Mariani et al, 1994;Pinotti et al, 2000) and the Arg353Gln polymorphism of exon 8 (Green et al, 1991). Iacoviello et al (1998) demonstrated in patients with myocardial infarction and family history of cardiovascular diseases, that the Gln353 allele of the Arg353Gln polymorphism and the 7(a) allele of the t a n d e m r e p e a t u n i t p o l y m o r p h i s m o f t h e hypervariable region 4 within intron 7 might have a protective effect on the risk of myocardial infarction.…”
Section: Thrombophilia 40mentioning
confidence: 99%
“…The F7 mutations À323P0/10 (10-bp insertion) and R353Q (dbSNP, ss#4328232; http://www.ncbi.nlm. nih.gov/SNP/snp_viewBatch) were analyzed by PCR as previously described [11,13]. For the À323P0/10, amplified products were electrophoresed on 8.0% polyacrylamide gel which permitted the identification of the 0-bp allele (204 bp) and the 10-bp allele (214 bp), and hence allowed us to deduce the genotype of the À323P0/10 carriers.…”
Section: Detection Of Fvii Mutationsmentioning
confidence: 99%
“…Several insertion-deletion and single-point mutations in the F7 gene were reported in the promoter region (e.g., À323P0/10) [10][11][12], within the transcribed space (e.g., R353Q point mutation) [13,14] and also within intronic (IVS7) sequences [7,15]. Insofar as plasma FVII levels vary significantly in the general population [16], as they are influenced by environmental and genetic factors [17,18], recent studies have linked the presence of these mutations in the FVII gene with plasma FVII levels [14,15] and activity [19].…”
Section: Introductionmentioning
confidence: 99%